Gesture Formalization for Multitouch. (6th December 2013) - Kammer, D.; Henkens, D.; Henzen, C.; Groh, R.
Summary Since multitouch interfaces are steadily moving out of the experimental niche, the demand for comprehensive programming support increases. Between the formation of de facto standards for multitouch gestures by the industry, and continued research and experimentation by developers or academia, the abstraction of gesture properties becomes essential. This paper contributes a revision of the Gesture Formalization for Multitouch (GeForMT) gesture description language. This language aims at a short and concise syntax, which is still able to capture the complexity of multitouch gestures. We report on a previously missing reference architecture and practical implementation. Based on a study comparing the revised GeForMT language with other formalization approaches for multitouch gestures, we introduce an editor for GeForMT.Copyright © 2013 John Wiley & Sons, Ltd.